Application of Reminiscence Therapy to Improve the Emotional Well-being and Social Engagement of Elderly Individuals with Dementia - Lamon, Chuanchen (International Journal on ObGyn and Health Sciences, 2025)
This research investigates the application of reminiscence therapy (RT) to improve the emotional well-being and social engagement of elderly individuals with dementia. RT, a non-pharmacological intervention that involves recalling personal memories, is recognized for its potential to reduce symptoms of depression and anxiety, while enhancing social interaction and overall quality of life. The study employed a mixed-methods approach, combining quantitative assessments of mood and anxiety levels with qualitative observations of participant engagement during RT sessions. The results revealed significant reductions in depressive and anxiety symptoms, as well as increased social interaction and communication among participants. Additionally, the study highlights the importance of cultural relevance and individualized approaches in the implementation of RT, particularly considering the variability in response based on the stage of dementia. Despite the positive outcomes, several practical challenges were identified, including resource limitations, the need for trained facilitators, and the emotional sensitivity required in managing distressing memories. The findings suggest that RT is an effective and promising intervention for dementia care, though its success relies on careful tailoring to individual needs and the availability of adequate resources and support. This research contributes to the growing body of evidence supporting the use of RT and calls for further exploration of its long-term effects, as well as strategies to overcome implementation barriers in diverse care settings.